2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27334
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Reflection Activities in a Chemical Engineering Course: Fundamentals of Heat and Mass Transfer

Abstract: This paper presents a quantitative and qualitative study for discovering how written reflective exercises following in-class prediction activities enhance learning gains in a heat and mass transfer course for chemical engineering undergraduate students. The primary purpose of this research is to determine if and to what extent written reflection plays a role in adjusting commonly-held misconceptions students have about heat and mass transfer. To study this, three 30-minute prediction activities were planned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…While some uses of reflection are not surprising, such as the development of ethical reasoning (Kisselburgh et al, 2016) and enhancing leadership competencies (Hendricks et al, 2018), other uses of reflection are emerging in a less likely place in the engineering curriculum: in foundational engineering science courses. For instance, reflection has been used to adjust students' commonly held misconceptions about heat and mass transfer (Chenette and Ribera, 2016) and help improve computer science students' detection of faults in software (Goswami and Walia, 2016).…”
Section: Learning Mechanismsmentioning
confidence: 99%
“…While some uses of reflection are not surprising, such as the development of ethical reasoning (Kisselburgh et al, 2016) and enhancing leadership competencies (Hendricks et al, 2018), other uses of reflection are emerging in a less likely place in the engineering curriculum: in foundational engineering science courses. For instance, reflection has been used to adjust students' commonly held misconceptions about heat and mass transfer (Chenette and Ribera, 2016) and help improve computer science students' detection of faults in software (Goswami and Walia, 2016).…”
Section: Learning Mechanismsmentioning
confidence: 99%
“…While the working hypothesis is that students who exhibited more critical reflection, thus making strides to adapt and change their way of thinking, were the students with the highest normalized learning gains, preliminary work was inconclusive 1 . It was shown that for Activity 1, there was "a weak correlation between the normalized gain score of individual students in this category and the level of reflection displayed by each student in the follow-up activity"…”
Section: Resultsmentioning
confidence: 99%
“…A detailed literature review of these subjects can be found in a previously published work-in-progress ASEE paper (Chenette and Ribera, 2016) 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been evidenced that participation in high-impact experiences can be life-changing for students [4]. Assessment of high-impact experiences is routinely accomplished using summative critical reflection [5][6][7][8][9][10][11].…”
Section: Literature Reviewmentioning
confidence: 99%